2011
DOI: 10.1167/iovs.11-7427
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Confocal Microscopy of Meibomian Glands in Contact Lens Wearers

Abstract: Morphologic changes in the MGs shown by LSCM were interpreted as signs of MG dropout, duct obstruction, and glandular inflammation. A comprehensive LSCM evaluation of the ocular surface in CLWs could better clarify the role of MG dropout and eyelid margin inflammation on the pathogenesis of CL-induced dry eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
5
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 23 publications
7
107
5
1
Order By: Relevance
“…Although most of the results from the present study agree with past studies on this topic, 13,35Y38 there were some disagreements. 13,35,36 For example, Villani et al's study 13 found TBUT and gland expressibility to be different between the two groups whereas the present study did not find a difference. Differences in results may have arisen because Villani et al 13 recruited symptomatic subjects whereas the present study mostly had normal subjects.…”
Section: Meibomian Gland Atrophy In Daily Contact Lens Wearersvpuckercontrasting
confidence: 70%
See 2 more Smart Citations
“…Although most of the results from the present study agree with past studies on this topic, 13,35Y38 there were some disagreements. 13,35,36 For example, Villani et al's study 13 found TBUT and gland expressibility to be different between the two groups whereas the present study did not find a difference. Differences in results may have arisen because Villani et al 13 recruited symptomatic subjects whereas the present study mostly had normal subjects.…”
Section: Meibomian Gland Atrophy In Daily Contact Lens Wearersvpuckercontrasting
confidence: 70%
“…13,35,36 For example, Villani et al's study 13 found TBUT and gland expressibility to be different between the two groups whereas the present study did not find a difference. Differences in results may have arisen because Villani et al 13 recruited symptomatic subjects whereas the present study mostly had normal subjects. An additional discrepancy was with Guillon and Maissa's work, 35 which determined that there was no significant difference in lissamine green staining between the two groups, and they found that the CL group was significantly more likely to have symptoms than the NCL group.…”
Section: Meibomian Gland Atrophy In Daily Contact Lens Wearersvpuckercontrasting
confidence: 70%
See 1 more Smart Citation
“…116 This LSCM study of meibomian glands showed significantly decreased basal epithelial cell density, lower acinar unit diameters, higher glandular orifice diameters, and greater inhomogeneity of the periglandular interstices in CL wearers compared with that in controls. These authors interpret such morphologic changes as signs of MGDo, duct obstruction, and glandular inflammation.…”
Section: Meibomian Gland Dropoutmentioning
confidence: 59%
“…Meibomian gland morphology can be evaluated by imaging methods such as infrared meibography [24 •• , 25-28, 29 •• ], optical coherence tomography (OCT) meibography [30, 31 • , 32], and in vivo confocal microscopy (IVCM) [33][34][35][36][37]. Meibography was first described in 1977 when Tapie described a basic method of eyelid transillumination, using a diaphanoscope with a red light filter to retroilluminate the meibomian gland silhouette that was observed with a slit-lamp microscope [38].…”
Section: Introductionmentioning
confidence: 99%